Biological services by Streptomyces lavendulae MTCC 706 to control invasion, development and reproduction of root-knot nematode (Meloidogyne incognita) infecting tomato cv Pusa Ruby - SELLAPERUMAL, C; KAMRA, ANJU; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2016)
The drench application of S. lavendulae MTCC706 @ 2% v/w (SLT) resulted in less than 50% juvenile invasion of M. incognita J2s in tomato (cv. Pusa Ruby), delayed development of J4s, 50.7% reduction in root galling and 42.7% reduction in egg mass production, compared to control. The reproduction factor was 1.2 in SLT, compared to 2.4 in control in 45 days. SLT was compatible with the nematicide carbofuran, as increase in bioefficacy of SLT was observed with 60% reduction in root galling, 61.5% reduction in egg mass production, and a reproduction factor of 1.1 in the combined application with carbofuran @0.5 kg a.i/ha. Replanting of tomato in the pre-treated soil revealed a further reduction in root galling (81.3%), egg mass production (80.5%) and reproduction factor (0.6), indicating establishment of the actinomycete in the soil.